Praṇavaprakāśa : hā oṅkāravicārarūpaparamārthavishayaka nibandha - Dāmale, Keśava Nārāyaṇa Śāstrī (Indirā Chāpakhānyānta, 1897)
On Om, its origin, significance, philosophical implications based on Hinduism.